Training quality and work motivation predict vocational high school teacher performance effectively - Marliza Deviana; Eko Indrawan; Ika Parma Dewi; Jonni Mardizal (Global Econedu, 2026)
This study examined the effects of Training Quality and Work Motivation on Teacher Performance among vocational high school teachers. A quantitative explanatory survey was conducted involving all 31 teachers at SMKN 7 Sijunjung using a census sampling technique. Data were collected through a structured questionnaire and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4.1.0.8. The measurement model demonstrated satisfactory reliability and validity. Training Quality had the strongest positive effect on Teacher Performance (β = 0.646, p < 0.001), followed by Work Motivation (β = 0.416, p < 0.001). Together, both variables explained 64.9% of the variance in Teacher Performance (R² = 0.649). Enhancing teacher performance requires integrating high-quality professional development with strategies that strengthen teachers' work motivation